Identification of a novel peptide targeting TIGIT to evaluate immunomodulation of 125I seed brachytherapy in HCC by near-infrared fluorescence - Zeng, Peng; Shen, Duo; Shu, Wenbin; Min, Shudan; Shu, Min; Yao, Xijuan; Wang, Yong; Chen, Rong (Frontiers in Oncology, 2023)
Hepatocellular carcinoma (HCC) has very poor prognosis due to its immunosuppressive properties. An effective measure to regulate tumor immunity is brachytherapy, which uses 125I seeds planted into tumor. T cell immune receptors with immunoglobulin and ITIM domains (TIGIT) is highly expressed in HCC. The TIGIT-targeted probe is expected to be an effective tool for indicating immunomodulation of 125I seed brachytherapy in HCC. In this study, we verified the expression of TIGIT by immunofluorescence (IF) and flow cytometry (FCM) in different part and different differentiated human liver cancer tissues. Then, we synthesized an optical fluorescence probe (Po-12) containing a near-infrared fluorescence (NIRF) dye and TIGIT peptide, for evaluating the modulatory effect of 125I seed brachytherapy. Lymphocytes uptake by Po-12 were detected by FCM and confocal microscopy. The distribution and accumulation of Po-12 in vivo were explored by NIRF imaging in subcutaneous and orthotopic tumors. IHC and IF staining were used to verify the expression of TIGIT in the tumors. The results showed that Po-12 could effectively bind to lymphocytes in tumors and indicated a change in TIGIT expression after 125I seed brachytherapy, which may have potential clinical value in determining the immune status of HCC in real time without invasive detection.